STRATEGI SINGAPURA DALAM PENGENDALIAN KONSUMSI TEMBAKAU PADA FRAMEWORK CONVENTION ON TOBACCO CONTROL (FCTC) TAHUN 2010-2014 - Nadhilah, Ega; Pahlawan, Indra (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
This research is a study of diplomatic which discusses about the strategy of Singapore to control the consumption of tobacco in Framework Convention on Tobacco Control (FCTC). Consumption of tobacco is not a new phenomenon in Singapore.This practice of tobacco’s consumption is known in past time. Tobacco’s consumption leads to harm not just the users but also the people’s around who breathe the air that polluted by tobacco.Victims generally come from any ages and member of families and they are vulnerable to be come affected by tobacco, risk of diseases that comes with consumption of tobacco such as cancer, heart attack, lung diseases, could harm pregnant woman , kids and teenagers. In this research, the author uses the nation analysis level  which focused on the strategy of Singapore. This research uses a realism perspective in international relations and strategy theory of John P.Lovell and diplomatic theory of William C.Olson. FCTC's strategy to control Tobacco consumption in Singapore by suppress and control tobacco consumption. In effort to control and suppress tobacco consumption in Singapore, Singapore join the Framework Convention on Tobacco Control (FCTC) for solid strategys and programs. The strategys and programs from FCTC’s are adopted to Singapore with the name of National Tobacco Control Program (NTCP). NTCP’s strategys and program and will be monitoring and evaluation by the Singapore government for better result and the consumption of tobacco decreasing from year to year. Keywords: tobacco consumption, tobacco control, the framework convention on tobacco control (fctc), control.